COMPARATIVE ANALYSIS OF PERFORMANCES IN BANKING SECTOR - MIRELA MONEA (Annals of the University of Petrosani: Economics)
Financial crisis had a major impact on economic development worldwide and the banking system as well. The main purpose of the paper is to present a comparative approach of the key drivers of bank performances. Discussions are related to banks profitability based on the literature review and researches related to drivers factors who may affects the activity in banking sector, and about trends of the profitability in banking system in European Union based on main profitability ratios: return on assets and return on equity.